Energy and daylighting performance of building integrated spirooxazine photochromic films. (August 2022) - Cannavale, Alessandro; Zampini, Giulia; Carlucci, Francesco; Pugliese, Marco; Martellotta, Francesco; Ayr, Ubaldo; Maiorano, Vincenzo; Ortica, Fausto; Fiorito, Francesco; Latterini, Loredana
Highlights: A novel photochromic (PC) film was developed and tested for smart windows. Building integration in a standard medium office building was modelled. Energy saving were assessed, comparing PC glazing with standard compliant glazing. Up to 4 MWh/year of energy saving and 40% of visual comfort increase were reached. The dynamic behaviour of the PC film is the best choice for visual comfort. Abstract: The study of chromogenic materials and systems is particularly promising for innovative, transparent building envelopes, with thermo-optical properties adaptable to surrounding environmental conditions. This work spots light on the multiple effects of photochromic glazing on the energy consumption of buildings and on the impact that such technologies would have on the visual comfort of occupants. To our knowledge, this is the first work dealing with building integration of spirooxazine-based photochromic films. This experimental and theoretical work aims helping to fill this gap by reporting the results of a study concerning the spirooxazine photochromic molecules, integrated in transparent matrices of polymethylmethacrylate. This work discloses the potential of specific photochromic materials, especially as a function of spectral peculiarities. The figures of merit of this technology have been studied by assuming its integration in an ideal multi-storey office building, and by studying the effects in terms of energy consumption and visual comfort and proposing a comparison with several static commercial glazing technologies. The photochromic glazing demonstrated to offer significant reduction of energy use for cooling, compared to a clear glass (with yearly saving of 4079 kWh, on the Southern facade), and for artificial lighting (with a saving of 3711 kWh), if compared to the commercial solar control glazing. Furthermore, the dynamic behaviour of the photochromic glazing represented the best choice in terms of visual comfort.